The Last of the Lost Generations? Formal and Non-Formal Education in Ghana during Times of Economic Decline and Recovery - Niels-Hugo Blunch; Jeffrey S. Hammer (Global Labor Organization (GLO), 2018)
Using a cohort approach, this paper examines educational attainment in Ghana and its potential determinants considering both educational attainment in the formal education system and participation in non-formal education in the form of adult literacy programs. The results indicate an overall substitution between formal and non-formal education across the generations, with participation in adult literacy programs decreasing as the formal education system expanded its coverage across space and time in Ghana. Individuals who completed any formal education were also much less likely to participate in adult literacy programs, by about 10 percentagepoints per year of formal education completed. Additionally, the generations subject to the declining education system during the 1970s were substantially disadvantaged, with the cohort that was roughly of primary school age at the time of the economic breakdown in 1983 and the first few years thereafter being the last of the disadvantaged cohorts—the “lost generations.” This is especially true for the particularly vulnerable group of individuals who never received any formal education, where the crisis cohort peaked in terms of adult literacy program participation relative to later (and earlier) cohorts, possibly in response to a decrease in the quality of the formal education system as well as increased competition from returning refugees. We perform a simple test for the declining quality of the formal education system in the 1970s and find evidence consistent with a decrease in the quality in the education system during the 1970s, followed by an increase in quality thereafter.
Keywords: I210; J240; 330; Human capital; formal and non-formal education; adult literacy programs; cohort analysis; Ghana